Accelerated Aging of Hommali Paddy by Drying in Sealed Container - Chinsuwan, Winit; Wannacharee, Poomisit (Engineering and Applied Science Research, 2013)
The objective of this study is to accelerate aging of Hommali paddy by drying, The results indicate that drying of the paddy in a sealed container with a temperature of at least 55ºC can accelerate aging. The use of higher temperature for drying or higher initial moisture contents of paddy result in less drying time. This aging process also results in higher percentage of head rice yield. Even though the whiteness is reduced but still in the acceotable limit by commercial standard. However, the aroma is lost